Assessing Environmental Law Awareness Among Bachelor of Elementary Education Students: A Study on Knowledge and Attitudes - Ibañez, Jr. , Roger Y.; Velza, Jacob Frederick P.; Amit, Demelyn S.; Mahawan, Alvin M. (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
The study aimed to investigate the level of knowledge and attitudes towards environmental laws among Bachelor of Elementary Education (BEED) students. A quantitative research design was utilized, and the primary data-gathering tool was a survey questionnaire. The study discovered that the BEED students had a generally poor level of knowledge, but their attitudes toward environmental laws were positive. The outcomes showed that only a few students were concerned about the environment and supported environmental protection, and a majority of them did not practice positive behavior. Despite knowing the penalties for violating environmental laws in the Philippines and the procedures for reporting environmental violations, many students continued their bad practices. Only a small proportion of them exhibited positive behavior or practices that supported environmental protection. Therefore, the BEED students at DEBESMSCAT, Cawayan, Campus had an insufficient and incomplete understanding of the environmental laws in the Philippines. The findings of the study highlighted the need to enhance the environmental education curriculum in the BEED program to improve the student's knowledge and attitudes toward environmental laws. As the students' knowledge and attitudes towards environmental laws could significantly impact their behavior and practices, it was essential to strengthen their comprehension of environmental laws and their role in environmental protection. The study emphasized the responsibility of academic institutions in promoting environmental education among students to ensure that they became environmentally responsible citizens in the future.